2002
DOI: 10.1046/j.1420-9101.2002.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Status-dependence and morphological trade-offs in the expression of a sexually selected character in the mite, Sancassania berlesei

Abstract: In the male dimorphic mite Sancassania berlesei, fighter males kill rivals with a pair of armoured legs whereas scrambler males are benign with unmodified legs. In an adaptive response mediated by colony pheromones, fighter expression increases at low colony density. Under the status-dependent evolutionarily stable strategy (ESS) model we expected heavier final instar nymphs to become fighters. This was supported in group reared nymphs. In individually reared nymphs fighter expression was experimentally suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 28 publications
7
108
1
Order By: Relevance
“…Knell et al 2004). In taxa where exaggerated structures become fixed at a particular moment in development, and in particular those developing adult morphology in a closed system such as holometabolous insects, the stage is set for resource competition (Klingenberg & Nijhout 1998;Nijhout & Emlen 1998;Emlen 2001;Radwan et al 2002;Moczek & Nijhout 2004). Equally, in such systems, the opportunity for selection to act on precise integration of traits that enable exaggerated structures to be borne and displayed is also clear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Knell et al 2004). In taxa where exaggerated structures become fixed at a particular moment in development, and in particular those developing adult morphology in a closed system such as holometabolous insects, the stage is set for resource competition (Klingenberg & Nijhout 1998;Nijhout & Emlen 1998;Emlen 2001;Radwan et al 2002;Moczek & Nijhout 2004). Equally, in such systems, the opportunity for selection to act on precise integration of traits that enable exaggerated structures to be borne and displayed is also clear.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have demonstrated that intra-organism competition occurs over resources devoted to somatic structures (Klingenberg & Nijhout 1998;Nijhout & Emlen 1998;Emlen 2001;Radwan et al 2002;Moczek & Nijhout 2004). These morphological trade-offs have, in particular, been demonstrated in species where alternative reproductive tactics give rise to dramatically divergent morphologies among males, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations